Tradisi Pa’seka Manyiang dalam Peringatan Maulid Nabi di Desa Tulehu: Sebuah Tinjauan Antropologi - Kamila Maryam Kotta; Marwiyah Rizkiyah Lestaluhu (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2025)
The Pa'seka Manyiang tradition is one of the traditions carried out by the people of Tulehu village, Salahutu sub-district, Central Maluku regency to commemorate the Prophet Muhammad's birthday. This tradition is carried out once a year by involving several clans in Tulehu village who also participate in the implementation of the tradition. The purpose of this study is to explain how the Pa'seka Manyiang tradition is carried out in commemorating the Prophet Muhammad's birthday in Tulehu village. The approach used in this study is cultural anthropology as its basic reference. This study uses a method or type of library research. The data collection technique in this study is documentation, namely searching for data on things or variables in the form of notes, books, papers or articles, journals that are related to anthropological studies and Pa'seka Manyiang. The results of this study indicate that the implementation of the Pa'seka Mayiang tradition is carried out with a series of customs that have been carried out from generation to generation, starting from gatherings between clans to closing with the Pausah event or rubbing charcoal on the face. The wisdom that can be taken from the implementation of the Pa'seka Manyiang tradition is to maintain the relationship between humans and their Creator and fellow creatures or what is known as the term Hablun minallah and Hablun minannas.